Tuning the Molecular Weight of Chlorine‐Substituted Polymer Donors for Small Energy Loss†. Issue 6 (10th May 2021) - Zhao, Tingxing; Wang, Huan; Pu, Mingrui; Lai, Hanjian; Chen, Hui; Zhu, Yulin; Zheng, Nan; He, Feng
Main observation and conclusion: The molecular weight of polymers plays a major role in their aggregation and miscibility in active layer, which eventually dominate the energy loss and device performance. A series of chlorine‐substituted PBD‐Cl polymers with controlled molecular weight have been synthesized as templates to discern a relationship between molecular weight and the optical properties, energy levels, morphologies, energy loss and photovoltaic performance. Although it has similar optical and electrochemical properties, when blended with acceptor N3, the low molecular weight polymer PBD‐ClL gives the biggest energy loss value, and a PCE of 12.06%. PBD‐ClH shows a moderate energy loss, but displays the lowest PCE of 9.00% as a result of excessive aggregation. PBD‐ClM with a medium molecular weight gives the smallest energy loss and achieves a PCE of 17.17%, which is among one of the highest values recorded to date for the Cl‐substituted polymer solar cells. Moreover, the molecular weight mainly affects the nonradiative energy loss (Δ E 3 ), PBD‐ClM also shows the smallest value of 0.252 eV among three polymer donors. These results show the effect of controlling the molecular weight to achieve a small energy loss and provide guidelines which can lead to an understanding of the real photovoltaic performance of new materials. Abstract :